8Th Century Musical Instrument on Kalasan Temple’s Relief - Pradoko, Susilo; Widyastuti, Maria Goretti; Fu'adi, Fu'adi; Walidaini, Birul (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
This research aims to unveil the types, size, figures, and functions of musical instruments carved as reliefs of Kalasan Temple as a way to revitalize the music from the 8th century. This research implements heuristic methods with Panofsky's iconology analysis in three steps, which are pre-iconography, iconography, and iconology to analyse the reliefs of the Temple. The researchers validated the findings through forum group discussion with the Cultural Heritage Preservation Board of Yogyakarta. The findings show that (1) the relief of musical instruments in Kalasan temple is located on the head of Kala; (2) the musical instruments on the head are two wind instruments made of shells and a stringed instrument named vina; (3) there are two figures of musicians carved, which are two wind instruments players and a player of stringed instruments. The figures are depicted as heavenly creatures named Gandharva; (4) the measurement shows that the wind instruments have 35.98 cm length and 12.85 cm width, another one has 23.13 cm length and 12.85 cm width. Meanwhile, the stringed instrument has a length of 92.52 cm and 12.85 cm width; and (5) the musical instruments were performed to worship the Goddess of Tara.